Where the speed matters... zero-response-time search engine for small collections - Gamage, Ruwan (Springer Berlin Heidelberg, 2005)
Users with slow internet connections experience slow retrieval of results in web catalogues. JavaScript search engines can be used to enable client side search, reducing the load on the server, and increasing the response time. However, it is not a popular method until now, because of various reasons including limitation of number of data objects and lengthier response time for the first search. Here the author suggests negotiating the issue of response delay with the user. This would enable high speed basic search in small catalogues, usually with less than 300 data objects. Larger catalogues can be divided into smaller ones. Special or rare collections, multimedia artifacts and subject (web) directories are prospective candidates for this type of search systems. A prototype catalogue of ‘Sri Lankan Web Sites’ was tested in www.srilankasupersearch.com. Users’ behavior and response to the system is yet to be studied.
Keywords: JavaScript; Search engines; Response time; Negotiation; OPAC; models